2014
DOI: 10.1021/ja501602t
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Networks in a (β/α)8 Barrel Enzyme Change during Catalytic Turnover

Abstract: Proteins can be viewed as small-world networks of amino acid residues connected through noncovalent interactions. Nuclear magnetic resonance chemical shift covariance analyses were used to identify long-range amino acid networks in the α subunit of tryptophan synthase both for the resting state (in the absence of substrate and product) and for the working state (during catalytic turnover). The amino acid networks observed stretch from the surface of the protein into the active site and are different between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(97 citation statements)
references
References 37 publications
3
93
1
Order By: Relevance
“…This proposition is in agreement with previous studies showing that the allosteric modulation of protein function is mediated by the propagation of 'perturbation waves' through pre-existing pathways interconnected by central residues [15,16,20,[24][25][26][27]. Similarly, RIN are relevant for structural changes involved in enzyme function [28]. Eyring plots were used to search for details of the mechanism by which the perturbation of central residues change the thermal denaturation of Sfbgly (Figs 13-15).…”
Section: Resultssupporting
confidence: 88%
“…This proposition is in agreement with previous studies showing that the allosteric modulation of protein function is mediated by the propagation of 'perturbation waves' through pre-existing pathways interconnected by central residues [15,16,20,[24][25][26][27]. Similarly, RIN are relevant for structural changes involved in enzyme function [28]. Eyring plots were used to search for details of the mechanism by which the perturbation of central residues change the thermal denaturation of Sfbgly (Figs 13-15).…”
Section: Resultssupporting
confidence: 88%
“…To probe the conformational transitions of the enzyme with the different nucleotides, we mapped the enzyme’s amide fingerprint using [ 1 H, 15 N]-TROSY-HSQC experiments (Pervushin et al, 1997) as the amide chemical shifts are sensitive reporters of allosteric transitions (Figure S5) (Axe et al, 2014; Cembran et al, 2014; Selvaratnam et al, 2011). Although previous crystallographic structures of these complexes were reported to be identical (Johnson et al, 2001), small changes in chemical shifts have been demonstrated to report on subtle changes in conformation and allostery (Boulton et al, 2014; Selvaratnam et al, 2012a; Selvaratnam et al, 2012b).…”
Section: Resultsmentioning
confidence: 99%
“…These long‐range networks may also offer means through which enzymes communicate in multi‐enzyme complexes . For example, we used NMR chemical shift covariance analysisamong a series of site‐directed protein variants to identify amino acid interaction networks in the alpha subunit of E. coli tryptophan synthase (αTS) . Our analysis revealed that there are two networks of residues [colored orange and blue in Fig.…”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 99%